2020
DOI: 10.1001/jamaneurol.2020.2734
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Psychological Outcomes of Disclosing Amyloid Imaging Results to Research Participants Who Do Not Have Cognitive Impairment

Abstract: The goal of preclinical Alzheimer disease (AD) clinical trials is to move diagnosis and treatment to presymptomatic stages, which will require biomarker testing and disclosure.OBJECTIVE To assess the short-term psychological outcomes of disclosing amyloid positron emission tomography results to older adults who did not have cognitive impairment. DESIGN, SETTING, AND PARTICIPANTSThis observational study included participants who were screening for a multisite randomized clinical trial that began on February 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 45 publications
8
96
0
Order By: Relevance
“…Specifically, both amyloid groups demonstrated increased scores for Item 7 (" To confirm the feeling that I might already be developing symptoms of Alzheimer’s disease dementia ”), whereas only those with not elevated amyloid demonstrated increased scores in Item 2 (" To put my mind at ease if I found out I do not have elevated amyloid on my PET scan ”), while those with elevated amyloid saw an average decrease in score for this item. Previously published results agree with this finding: participants with elevated amyloid similarly demonstrated no change on the FTP scale after biomarker disclosure 6 . In the SOKRATES study, participants learning an elevated amyloid result felt that the result validated their memory concerns, compared to participants with not elevated amyloid who reinterpreted memory concerns as normal aging 9 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Specifically, both amyloid groups demonstrated increased scores for Item 7 (" To confirm the feeling that I might already be developing symptoms of Alzheimer’s disease dementia ”), whereas only those with not elevated amyloid demonstrated increased scores in Item 2 (" To put my mind at ease if I found out I do not have elevated amyloid on my PET scan ”), while those with elevated amyloid saw an average decrease in score for this item. Previously published results agree with this finding: participants with elevated amyloid similarly demonstrated no change on the FTP scale after biomarker disclosure 6 . In the SOKRATES study, participants learning an elevated amyloid result felt that the result validated their memory concerns, compared to participants with not elevated amyloid who reinterpreted memory concerns as normal aging 9 .…”
Section: Discussionsupporting
confidence: 62%
“…Although participants with not elevated amyloid did not increase their endorsement of Planning/Preparation as much as those with elevated amyloid, they did demonstrate an absolute increase in endorsement of these items. It is possible that this could have been in response to planning for a future that was less likely to include dementia, since it has been shown that these participants also demonstrated an increase in Future Time Perspective (FTP) scale score 6 …”
Section: Discussionmentioning
confidence: 99%
“…In the absence of unique interventions to modify disease risk, there is a concern that full disclosure may lead to unnecessary worry or anxiety. Counter to this, a recent study on disclosing abnormal amyloid imaging, a biomarker of Alzheimer’s disease risk, to cognitively healthy older adults did not find a short-term effect on depression or anxiety symptoms or suicidal ideation [ 28 ]. However, this study excluded from disclosure those with moderate to severe depression or anxiety symptoms or history of suicidal ideation [ 28 ], and these are the patients who may have the most severe adverse outcomes from disclosure.…”
Section: Disclosure Of Neurodegeneration Risk In Irbdmentioning
confidence: 99%
“…Counter to this, a recent study on disclosing abnormal amyloid imaging, a biomarker of Alzheimer’s disease risk, to cognitively healthy older adults did not find a short-term effect on depression or anxiety symptoms or suicidal ideation [ 28 ]. However, this study excluded from disclosure those with moderate to severe depression or anxiety symptoms or history of suicidal ideation [ 28 ], and these are the patients who may have the most severe adverse outcomes from disclosure. In those at risk for Alzheimer’s disease, about 20% in one study indicated a desire to pursue physician-assisted death if they become cognitively impaired [ 29 ].…”
Section: Disclosure Of Neurodegeneration Risk In Irbdmentioning
confidence: 99%
“…This requirement has been reported to be a greater barrier for Black participants than their White counterparts 21 and is concordant with observations in AD dementia trials, where Hispanic and non-White participants are more likely to have nonspouse study partners (eg, caregivers). 32 Increased understanding of the attitudes of multiethnic groups toward the study partner requirement, as well as toward other unique aspects of participating in preclinical AD trials (eg, the requirement of amyloid biomarker disclosure 33 ), should be prioritized to improve study designs and recruitment efforts.…”
Section: Quantify Site and Central Recruitment Efforts And Costsmentioning
confidence: 99%